KEḤUJJAHAN HADIS ĀḤĀD DAN IMPLIKASINYA TERHADAP NĀSIKH MANSŪKH - Andaluzi, Fahmi; Millah, Musidul; Alif, Muhammad (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
The dialectic surrounding hadith as an authoritative source in Islam, one of which is motivated by the emergence of mutawātir and āḥād dichotomy to judge hadith based on the quantity of its narrators. Some figures or circles still question the authorization of the āḥād hadith and tend to reject it. Although the majority of scholars recognize the authority of the hadith āḥād and refute the argument against it, in its theory and application it is quite complex, such as its authority in nāsikh-mansūkh as a method in the settlement of ta'arruḍ al-adillah is still a topic of discussion. This paper will explore the validity of āḥād hadith as the basis of Islamic law and its application in the theory of nāsikh-mansūkh, this research fully uses the method of library research by collecting relevant books and scientific articles then inventorying the arguments of scholars related to the validity of āḥād hadith and analyzing its position in nāsikh-mansūkh. The results of this study show that āḥād hadith that has met the established criteria must be accepted and practiced as a source of Islamic law. As for the position of āḥād in nāsīkh-mansūkh, it is generally divided into two parts. First, āḥād hadiths as mansūkh can be superseded by the Quran, mutawātir hadiths and āḥād hadiths. Secondly, an āḥād hadith as a nāsikh only supersedes other āḥād hadiths, while for superseding Quranic verses or mutawātir hadiths, the majority of scholars are of the opinion that it is only permissible according to reason. In other words, rationally, āḥād hadiths can supersede mutawātir hadiths verses and Quranic, because both are revelations from Allah. However, in practice, this is not the case, unlike some circles such as al-Ẓāhiriyyah who think that in reality there are āḥād hadith that supersede mutawātir.